Empowering Muslimat NU Activities through Hadroh Art Training as a Medium of Islamic Propagation in Bumi Harapan Village - Imam Royani Hamzah; Siti Khusnia; Prety Shinta (CV. Jalan Cendikia, 2026)
This community service program aimed to assist Muslimat NU in SP 1 Bumi Harapan Village by providing hadroh art training as a medium to strengthen religious activities, women’s empowerment, and cultural da’wah. The program employed a participatory community engagement approach through five stages: needs assessment, program planning, training and mentoring, community practice, and evaluation and follow-up. The results showed that Muslimat NU had strong socio-religious capital but still needed a wider variety of Islamic art-based activities due to the limited availability of hadroh trainers. The mentoring program improved participants’ basic skills in playing hadroh, reciting shalawat collectively, maintaining rhythmic harmony, and performing hadroh in the selapanan religious gathering. The program also strengthened participants’ confidence, group solidarity, courage to perform, and women’s participation in socio-religious activities. These findings suggest that Islamic art-based community service can be a participatory, contextual, and sustainable model for empowering women’s religious communities and strengthening cultural da’wah at the grassroots level.